Assessing regional variability in chemical composition and pozzolanic reactivity of corn stover ash in the United States - Mahmoud Shakouri; Jiong Hu; Cody Stolle (Cement, 2023)
This study examines the regional variability in the chemical composition and pozzolanic reactivity of corn stover ash (CSA) produced from corn stover samples collected from different locations in the U.S. Corn stover samples were collected from local farms in Nebraska and Iowa, while information about Kansas CSA was obtained from existing literature. The findings reveal significant variability in the chemical composition of untreated CSA across different regions. However, through the use of pretreatment techniques such as acid soaking, the compositional variations can be considerably reduced. The results of the modified R3 test demonstrate that CSA exhibits pozzolanic behavior that falls between that of fly ash and silica fume. The reactivity of CSA was found to be independent of geospatial factors but heavily influenced by the specific pretreatment methods employed in the study. Furthermore, the study indicates that the reactivity of CSA is less variable compared to fly ash and silica fume.